Reframing risks in rare diseases: economics of networks, spillovers, and scale - Runge, Carlisle Ford; Campbell, James; Runge, Carlisle P. (Frontiers in Pharmacology, 2024)
Rare diseases affect over three hundred million individuals globally. Investment in research and development remains incommensurate with the challenges rare diseases pose. Further investment in information sharing platforms to promote common and standardized network technologies for rare disease is needed. Rare disease R&D generates information and assets that spill over in other ways, providing benefits that may not be apparent to investors ex ante. Analytical and computational methods recently applied at scale are promising. One important way of achieving efficiencies of scale in R&D is clustering rare diseases into groups with similar traits.